Epidemiological profile of occupational ocular injury in a tertiary eye care centre of North India - Dahiya, Monika; Dua, Mohit (International Journal Of Community Medicine And Public Health, 2020)
Background: Occupational ocular injuries are quite common among industrial and agricultural workers. It is an important cause of preventable vision loss in developing as well as developed countries. The principal objective of our research work was to study epidemiological profile of occupational ocular injuries and use of protective eye wear at workplace in North India. Methods: A prospective, hospital based observational study was conducted on 400 patients of occupational ocular injuries attending emergency services and OPD in Regional Institute of Ophthalmology, PGIMS Rohtak, Haryana, India during June 2016 to March 2020. Results: Out of 400 patients of occupational ocular injuries, majority were male (92%) and most common age group affected was 31-40 years (48%) followed by 21-30 years (30%). Most common injured patients were of manufacturing industry (45%) followed by construction site (30%) and agriculture based industry (25%). Metallic foreign body (70%) was found to be the most common cause of occupational ocular injury in 70% cases followed by chemical injury in 10% cases. Ocular injuries were more common in temporary workers (65%) who were not having proper safety training and not using protective devices at workplace. Conclusions: Occupational ocular injuries most commonly affect young productive population leading to temporary or permanent vision loss. Avoidance of protective glasses and lack of basic safety training make them more vulnerable for ocular injuries. Therefore, all workers should be encouraged to adopt basic safety measures and proper safety training should be given to them. It will not only help in reducing the ocular morbidity, but will also enhance the economic productivity.